Dynamic changes in the pancreatitis activity scoring system during hospital course in a multicenter, prospective cohort. Issue 9 (18th February 2021) - Paragomi, Pedram; Tuft, Marie; Pothoulakis, Ioannis; Singh, Vikesh K; Stevens, Tyler; Nawaz, Haq; Easler, Jeffrey J; Thakkar, Shyam; Cote, Gregory A; Lee, Peter J; Akshintala, Venkata; Kamal, Ayesha; et al.
Abstract: Background and Aim: The primary aim was to validate the Pancreatitis Activity Scoring System (PASS) in a multicenter prospectively ascertained acute pancreatitis (AP) cohort. Second, we investigated the association of early PASS trajectories with disease severity and length of hospital stay (LOS). Methods: Data were prospectively collected through the APPRENTICE consortium (2015–2018). AP severity was categorized based on revised Atlanta classification. Delta PASS (ΔPASS) was calculated by subtracting activity score from baseline value. PASS trajectories were compared between severity subsets. Subsequently, the cohort was subdivided into three LOS subgroups as short (S‐LOS): 2–3 days; intermediate (I‐LOS): 3–7 days; and long (L‐LOS): ≥7 days. The generalized estimating equations model was implemented to compare PASS trajectories. Results: There were 434 subjects analyzed including 322 (74%) mild, 86 (20%) moderately severe, and 26 (6%) severe AP. Severe AP subjects had the highest activity levels and the slowest rate of decline in activity ( P = 0.039). Focusing on mild AP, L‐LOS subjects (34%) had 28 points per day slower decline; whereas, S‐LOS group (13%) showed 34 points per day sharper decrease compared with I‐LOS (53%; P < 0.001). We noticed an outlier subset with a median admission‐PASS of 466 compared with 140 in the rest. Morphine equivalent dose constituted 80% of the total PASS in the outliers (median morphine equivalent dose score = 392), compared with only 25% in normal‐range subjects (score = 33, P value < 0.001). Conclusions: This study highlighted that PASS can quantify AP activity. Significant differences in PASS trajectories were found both in revised Atlanta classification severity and LOS groups, which can be harnessed in AP monitoring/management (ClincialTrials.gov number, NCT03075618).